HYBRID SYSTEM OF DUAL AXIS PHOTOVOLTAIC TRACKING SYSTEM USING PID-CES-ACO - Machrus Ali; Rukslin Rukslin; Cholil Hasyim (Merdeka Malang University, 2021)
In this paper, the efficiency of photovoltaic panels is improved by adding two solar tracking systems. The solar tracking system is used to track the sun so that the photovoltaic always faces the sun. This system uses a dual axis consisting of a horizontal rotation axis and a vertical rotation axis. The motion of the horizontal axis of rotation follows the sun's azimuth angle from north to south. The motion of the vertical axis of rotation following the sun's azimuth angle from east to west is the vertical axis motion. Both types of movement are controlled using PID and Fuzzy controllers which are optimized with an artificial intelligence approach, namely Ant Colony Optimization (ACO). Experiments with PID control approach and CES control were optimized using the ACO method (Hybrid PID-CES-ACO method). In this research, PID-CES-ACO was the best model, obtained on the horizontal axis of overshot 1328 pu, the smallest undershot was 0.116, and the fastest settling time was 0.183 s, on the vertical axis the smallest overshot was 1.246 pu, the smallest undershot was 0.044, the fastest settling time was 0.163 s